Analysis Of Factors Affecting Economic Growth In Banten Province - Riko Dwi Saputra; Muhammad Rusdi (UNIVED Press, 2024)
This study aims to identify the factors that drive economic growth in Banten Province.The scope of this survey covers 8 districts in Banten Province.The data used are secondary data and cross sectional data. The results of the study indicated that there was a positive and significant relationship between the variables of labor force and government expenditure and economic growth, while unemployment had a significant negative effect on economic growth. The results showed that the variables of labor force, government expenditure and unemployment had a significant effect on economic growth in Banten Province.